Diversidade, narrativas de si e o ensino remoto: Um relato de experiências na formação de professores no PIBID Música da UEMG - Nelson Rodrigues Pombo Junior (2024)
In this research, In this research, the importance of an education that values differences, considering the various dimensions and pluralities that compose human identity, is emphasized. In the specific context of music education, the Institutional Program of Teaching Initiation Scholarships (PIBID) of the State University of Minas Gerais (UEMG), Arts-Music and Diversity Subproject, aimed primarily at diversity education. The PIBID occurred during school closures due to isolation, in an emergency remote teaching format (ERE). This dissertation is a narrative from my perspective, where I served as a Supervisor Teacher and contributed as a researcher. The program will be discussed as a public policy aimed at professionalizing music teachers in initial and ongoing education. The intention of this study is to contribute to the debate on the importance of PIBID in Music, presenting how interventions occurred in a public high school, without intending to serve as a model, but demonstrating its organization and implementation. The subproject aimed to discuss inclusive and diverse education, valuing multiple forms of musical expression and promoting a more critical and emancipatory teacher education. The methodological procedures adopted in the program included the study of autobiographical narratives, following the references of Kolb-Bernardes and Ostetto (2015), which were fundamental in the production of the dissertation, relating moments of my journey as an artist, musician, teacher and researcher, fundamental to the formation of my professional identity. During data collection, reports and lesson plans prepared by scholarship holders, undergraduate education students, meeting minutes, diagnostic observations, interventions, and educational activities in schools were examined. The aim is to enrich the debate on PIBID, considering it a significant public policy, with the purpose of strengthening its consolidation and highlighting its importance. To support this reflection, authors and theoretical references discussed within PIBID and those relevant to the subproject's themes from various perspectives were consulted. Among educational thinkers, Paulo Freire (2002) and António Nóvoa (2017) stand out. In the field of music education, Violeta de Gainza's (2015) ideas are considered, as well as authors who analyze school contexts from a sociological perspective, such as Margarete Arroyo (2002), and contributions from Helena Lopes da Silva and José Baeta Zille (2015). The PIBID Music is discussed by Nair Pires (2015), Marino and Rodrigues (2018), and Cibele Lauria da Silva (2021). Regarding music pedagogy, soundscapes, and the role of the music teacher, Murray Schafer (2011), and contributions from Cecília França (2015) were reviewed. The approach to diversity within the subproject, including Luis Ricardo Silva Queiroz (2024) as a significant source, along with other texts discussed within the professional master's program, was also examined.